2018
DOI: 10.1038/s41419-018-0784-6
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate as a potential “survival factor” in an in vitro model of neuronal hypoxia/reoxygenation injury: leading role of the Na+/Ca2+ exchanger

Abstract: In brain ischemia, reduction in oxygen and substrates affects mitochondrial respiratory chain and aerobic metabolism, culminating in ATP production impairment, ionic imbalance, and cell death. The restoration of blood flow and reoxygenation are frequently associated with exacerbation of tissue injury, giving rise to ischemia/reperfusion (I/R) injury. In this setting, the imbalance of brain bioenergetics induces important metabolic adaptations, including utilization of alternative energy sources, such as glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 62 publications
4
42
0
Order By: Relevance
“…14,15 Particularly, this cell line is used to develop the in vitro OGD/IR model. [15][16][17][18][19][20][21] Current findings in regenerative medicine have strengthened the search for new stem cell sources with beneficial properties; in particular, amniotic fluid has been identified as a valid resource of stem cells in this field. Adult stem cells, even after reprogramming, could preserve epigenetic alterations, thus representing a limitation in their application.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Particularly, this cell line is used to develop the in vitro OGD/IR model. [15][16][17][18][19][20][21] Current findings in regenerative medicine have strengthened the search for new stem cell sources with beneficial properties; in particular, amniotic fluid has been identified as a valid resource of stem cells in this field. Adult stem cells, even after reprogramming, could preserve epigenetic alterations, thus representing a limitation in their application.…”
Section: Introductionmentioning
confidence: 99%
“…Upon induction for a period of 8 days, RNLCs exhibited morphological alteration showing elongated structure, neuron-like axonal spread out and cell-cell contacts. Additionally, we found a significant upregulation in neuro-signalling molecules like l -glutamate, Ach and NO that also act as paracrine factors in retina and facilitate cell interactions [ 39 41 ]. qPCR results showed that RNLCs also exhibited an upregulation in a few neuronal and retinal markers (IRBP and RHO mRNA).…”
Section: Discussionmentioning
confidence: 99%
“…We also find that RNLCs have the potential to secrete neurotransmitters like nitric oxide, acetylcholine and l -glutamate in vitro, which also have a broad range of paracrine signalling function in neurons besides synaptic functions [ 39 41 ] (Sup Fig. 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that in different cell models and experimental settings, glutamate supplementation stimulates ATP synthesis under pathophysiological conditions [38][39][40][41]. Remarkably, this glutamate-related response strictly relies on the activity of two main players: Na + -dependent excitatory amino acid transporters (EAATs) and the Na + /Ca 2+ exchanger (NCX).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have previously demonstrated a physical and functional interaction between a specific EAATs subtype, EAAT3 (excitatory amino acid carrier 1, EAAC1 in rodents) and NCX1 at both the plasma membrane and the mitochondrial levels [38,41,50]. In both cardiac and neuronal models, their interaction modulates the glutamate-driven ATP synthesis under pathophysiological conditions [38][39][40][41]51].…”
Section: Introductionmentioning
confidence: 99%